Elevated Expression of JMJD5 Protein Due to Decreased miR-3656 Levels Contributes to Cancer Stem Cell-Like Phenotypes under Overexpression of Cancer Upregulated Gene 2 - Natpaphan Yawut; Il-Rae Cho; Phatcharaporn Budluang; Sirichat Kaowinn; Chutima Kaewpiboon; Byeol-Eun Jeon; Sang‐Woo Kim; Ho Young Kang; Min-Kyung Kang; Sang Seok Koh; Young–Hwa Chung (Biomolecules, 2022)
Overexpression of cancer upregulated gene (CUG) 2 induces cancer stem cell-like phenotypes, such as enhanced epithelial-mesenchymal transition, sphere formation, and doxorubicin resistance. However, the precise mechanism of CUG2-induced oncogenesis remains unknown. We evaluated the effects of overexpression of CUG2 on microRNA levels using a microRNA microarray. Levels of miR-3656 were decreased when CUG2 was overexpressed; on the basis of this result, we further examined the target proteins of this microRNA. We focused on Jumonji C domain-containing protein 5 (JMJD5), as it has not been previously reported to be targeted by miR-3656. When CUG2 was overexpressed, JMJD5 expression was upregulated compared to that in control cells. A 3' untranslated region (UTR) assay revealed that an miR-3656 mimic targeted the JMJD5 3'UTR, but the miR-3656 mimic failed to target a mutant JMJD5 3'UTR, indicating that miR-3656 targets the JMJD5 transcript. Administration of the miR-3656 mimic decreased the protein levels of JMD5 according to Western blotting. Additionally, the miR-3656 mimic decreased CUG2-induced cell migration, evasion, and sphere formation and sensitized the cells to doxorubicin. Suppression of JMJD5, with its small interfering RNA, impeded CUG2-induced cancer stem cell-like phenotypes. Thus, overexpression of CUG2 decreases miR-3656 levels, leading to upregulation of JMJD5, eventually contributing to cancer stem cell-like phenotypes.
Keywords: Cancer-related molecular mechanisms research; MicroRNA in disease regulation; RNA modifications and cancer